The Cardioprotective Effect of Leonurine in Hearts - Li, Z.Y.; Chen, LZ; Liu, YX; Zhu, Y.Z. (Cardiology and Cardiovascular Medicine, 2020)
Myocardial fibrosis is a common cardiovascular disease with a complex mechanism. Myofibroblasts and extracellular matrix play a key role in myocardial fibrosis. Leonurine, extracted from Herba Leonuri, plays a protective role in the pathogenesis and development of cardiovascular dieseses especially myocardial fibrosis. Undoubtedly, Leourine was considered as the potential therapeutic medicine of myocardial fibrosis in the future. However, the pathogenesis of leonurine on myocardial fibrosis remains unclear. The purpose of this review attempts to discuss the molecular mechanisms involved in the cardioprotective effects of Leonurine.